PERFORMANCE EVALUATION OF IEEE 802.11AC WIRELESS NETWORKS WITH QOS FOR MULTIMEDIA APPLICATIONS - Ahmed Hassan Mohammed (Journals Park Publishing, 2024)
The development of technologies related to wireless communication caused the worldwide utilization of (WLANs). IEEE 802.11ac offers several optimizations in the physical and MAC layers to make effots in higher throughput and optimized reliability. Consequently, (QoS) is a main method for efficaciously improving the performance of wireless networks. It is widely utilised in numerous real-time applications, like audio and video stream, while preserving network reliability and fairness. This work stresses on analysing the impacts of QoS on the performance of IEEE 802.11ac WLANs, particularily in both terms (throughputting and delaying). By employing the new software (Riverbed Modeller 18.5), three different numbers of nodes (4, 12, and 24 nodes) with unitary topologies are effectively modeled and efficaciously simulated to meticulously detect the WLANs performance for innumerable MIMO configurations. The simulation findings uncovered that applying QoS applications with a bandwidth of 80 MHz can improve throughput and delay performance. The better improvements in QoS (throughput and delay) values are acquired in the greatest number of nodes (24 nodes). For MIMO (3×3) spatial streaming, the improvement values are (98.2%) and (49.5%) for velocity (throughput) and latency (delay), respectively.
Keywords: Bandwidth, IEEE802.11ac, Riverbed v.18.5, Wireless LAN, QoS.